Money markets, central bank balance sheet and regulation - Stefano Corradin; Jens Eisenschmidt; Marie Hoerova; Tobias Linzert; Glenn Schepens; Jean-David Sigaux (European Central Bank (ECB), 2020)
This paper analyses money market developments since 2005, and examines factors that have affected money market functioning. We consider several metrics of activity in both secured and unsecured euro area money markets, and study interactions with new Basel III regulations and with central bank policies (liquidity provision, asset purchases and the Securities Lending Programme). Using aggregate data, we document that, prior to 2015, heightened financial market volatility coincided with worsening money market conditions, while higher central bank liquidity provision was associated with reduced money market stress. After 2015, the evidence is consistent with central bank asset purchases inducing scarcity effects in some money market segments, and with active securities lending supporting money market functioning. Using transactions-level money market data combined with supervisory data, we further document that the leverage ratio regulation impacts money markets at quarter-ends due to "window-dressing" effects, reducing money market volumes and rates. We also consider the macroeconomic impact of changing money market conditions, finding that the impact depends on whether frictions originate in secured or unsecured markets and on central bank policies in place.
Keywords: E44; E58; G12; G20; G28; 330; Money markets; asset purchases; securities lending; leverage ratio; liquidity coverageratio